The Resurgence of Cianjur Earthquake Adolescent Survivors: The Role of Coping Mechanisms and Resilience - Zahrani, Fanisya Triputri; Aini, Silvia; Firjatullah, Clarista Tertia; Faizah, Fida Salimah Al; Islaha, Shafia (Jurnal Psikologi Teori dan Terapan, 2024)
Background: Indonesia is situated on three major tectonic plates, making it highly susceptible to earthquakes. These disasters can cause significant material and psychological damage. Coping mechanisms are crucial for dealing with the stress following an earthquake, as they influence positive psychological changes. Research also shows that resilience affects psychological recovery after disasters. Objective: This study aims to examine the mediating role of resilience in the relationship between coping mechanisms and post-traumatic growth among adolescent earthquake survivors. Method: A quantitative descriptive approach was used with 201 high school students from the Cianjur District, selected through purposive sampling. Data were collected using the Brief-COPE for coping mechanisms, RS-14 for resilience, and PTGI-SF for post-traumatic growth. Results: The results show significant direct relationships between the variables. The direct effect of coping mechanisms on post-traumatic growth is 42.4%, while the effect through resilience is 10.9%. Conclusion: Resilience does not mediate the relationship between coping mechanisms and post-traumatic growth. The study highlights the importance of focusing on coping mechanisms to enhance post-traumatic growth in adolescent earthquake survivors.